Nanotechnology-based Nose-to-brain Delivery in Epilepsy: A Novel Approach to Diagnosis and Treatment - Khan, Javed; Yadav, Shikha (Pharmaceutical Nanotechnology, 2024)
Epilepsy is a serious neurological disease, and scientists have a significant challenge in developing a noninvasive treatment for the treatment of epilepsy. The goal is to provide novel ideas for improving existing and future anti-epileptic medications. The injection of nano treatment via the nose to the brain is being considered as a possible seizure control method. Various nasal medicine nanoformulations have the potential to cure epilepsy. Investigations with a variety of nose-to-brain dosing methods for epilepsy treatment have yielded promising results. After examining global literature on nanotechnology and studies, the authors propose nasal administration with nanoformulations as a means to successfully treat epilepsy. The goal of this review is to look at the innovative application of nanomedicine for epilepsy treatment via nose-to-brain transfer, with a focus on the use of nanoparticles for load medicines. When nanotechnology is combined with the nose to brain approach, treatment efficacy can be improved through site specific delivery. Furthermore, this technique of administration decreases adverse effects and patient noncompliance encountered with more traditional procedures.
Keywords: nanocarriers